Virtual AM Stereo and Surround Sound to setup AM/FM Radio Theatre - Selvakumaran Vadivelmurugan; Veeraraghavan Krishnan (Journal of Systemics, Cybernetics and Informatics, 2003)

(untitled)
Introduction of virtual surround sound and stereo to AM radio has been proposed in this study. This technology can be further applied to aid the construction of an AM radio theatre. Adding to the advantages of AM, the lower bandwidth, higher range and simpler circuitry, AM can now offer excellent sound effect with the post-transmission process. The motivation for the introduction of virtual surround sound is the poor quality of AM sound. In this study, the response by human ear has been thoroughly investigated and the methodology to create virtual surround sound has been developed. The elements essential to setup audio theatre such as the components of audio chain, multiple unit audio speaker, inner section of the ear, psychological effect of different ranges of frequency and radio theatre design have been extensively studied on the basis of Helmholtz audition theory. The vital changes include the different frequency division multiplexing of message at the transmitting end, three phases of the process, resulting in the vertical and horizontal digital connection, espresso program and the 3x12 speaker design theatre.